Prevalence and associated factors of nosocomial infection among children admitted at Jimma Medical Center, Southwest Ethiopia: a retrospective study - Jima, Serkalem Aschalew; Gerete, Tamirat Beyene; Hailu, Fikadu Balcha; Ayane, Girma Bacha; Jatu, Merga Garoma; Hardido, Temesgen Geta; Tolosa, Elias kenea (Frontiers in Pediatrics, 2025)
BackgroundNosocomial infections are a significant public health problem worldwide, affecting hundreds of millions of patients annually. However, studies on nosocomial infections specifically focused on pediatric patients in Ethiopia are limited. Therefore, this study aimed to assess the prevalence of nosocomial infections and associated factors among children admitted at Jimma Medical Center, southwest Ethiopia.MethodsAn institution-based retrospective cross-sectional study design was conducted from June 1 to 30, 2023. Data were collected from the medical records of children. A systematic random sampling technique was employed to select a total of 417 medical records. Data were collected using structured checklists. The collected data were entered into Epi-data version 4.6, and Statistical Package for Social Science version 26.0 was used for analysis. The variables with a p-value less than 0.05 were considered as statistically significant.ResultsA total of 417 (92.87%) medical records of the pediatric patient the inclusion criteria. Of these, 99 (23.74%) of pediatric patients developed nosocomial infections. Malnutrition [AOR = 2.01; 95% CI: 1.18, 3.42], length of hospital stay [AOR = 3.19; 95% CI: 1.73, 5.90], antibiotics received at admission [AOR = 4.76; 95% CI: 1.86, 12.15], being on mechanical ventilation [AOR = 5.04; 95% CI: 2.44, 10.43], blood transfusion [AOR = 4.51; 95% CI: 2.43, 8.35], and urinary catheter [AOR = 3.26; 95% CI: 1.72, 6.18] were significantly associated.ConclusionThe findings of this study indicated that nearly a quarter of children developed nosocomial infections. Malnutrition, length of hospital stay, antibiotics received at admission, being on mechanical ventilation, urinary catheter, and blood transfusion contributed to the development of nosocomial infections. Therefore, the concerned bodies should immediately prevent nosocomial infections and improve identified factors.